Atrial Fibrillation: Epidemiology, Pathophysiology, and Clinical Outcomes. Issue 9 (28th April 2017) - Staerk, Laila; Sherer, Jason A.; Ko, Darae; Benjamin, Emelia J.; Helm, Robert H.
Abstract : The past 3 decades have been characterized by an exponential growth in knowledge and advances in the clinical treatment of atrial fibrillation (AF). It is now known that AF genesis requires a vulnerable atrial substrate and that the formation and composition of this substrate may vary depending on comorbid conditions, genetics, sex, and other factors. Population-based studies have identified numerous factors that modify the atrial substrate and increase AF susceptibility. To date, genetic studies have reported 17 independent signals for AF at 14 genomic regions. Studies have established that advanced age, male sex, and European ancestry are prominent AF risk factors. Other modifiable risk factors include sedentary lifestyle, smoking, obesity, diabetes mellitus, obstructive sleep apnea, and elevated blood pressure predispose to AF, and each factor has been shown to induce structural and electric remodeling of the atria. Both heart failure and myocardial infarction increase risk of AF and vice versa creating a feed-forward loop that increases mortality. Other cardiovascular outcomes attributed to AF, including stroke and thromboembolism, are well established, and epidemiology studies have championed therapeutics that mitigate these adverse outcomes. However, the role of anticoagulation for preventing dementia attributed to AF is less established. Our review is a comprehensive examination of the epidemiological data associating unmodifiable and modifiable risk factors for AF and of the pathophysiological evidence supporting the mechanistic link between each risk factor and AF genesis. Our review also critically examines the epidemiological data on clinical outcomes attributed to AF and summarizes current evidence linking each outcome with AF.